Influence of heating temperature on structural properties of sol-gel materials - Bauer, Joanna; Ulatowska-Jarża, Agnieszka; Podbielska, Halina; Lechna-Marczyńska, Monika; Bindig, Uwe; Müller, Gerhard; Beuthan, Jürgen (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
In this paper, the influence of heating temperature on the properties of sol-gel materials was investigated . The aim of the study was to examine the production repeatability. All samples were made with factor R = 15, denoting the ratio of the number of precursor (TEOS) moles to solvent (water) moles. The samples were prepared in acid hydrolysis route on water, whereas two groups were considered: in one group the hydrolysis was terminated by addition of NH3·H2O and in the other there was no addition of base. The samples were stored for 1 month at room temperature and then exposed to high temperatures: 1000, 1200 and 1350°C. They were examined by means of scanning electron microscopy (SEM). The electron microphotographs were recorded, digitized and analyzed. The Fisher linear discriminant analysis for evaluation of the microscopic images was exploited. It was shown that the repeatability varied between 83.24% and 95.48%. The analysis demonstrated that the best results were achieved for neutralized samples made at 1000°C.
Optica Applicata, Vol. 35, 2005, nr 4, s. 791-797
Keywords: optyka; sol-gel; scanning electron microscopy (SEM); repeatability; Fisher linear discriminant analysis